Pengaruh Komunikasi Kerja Terhadap Kinerja Karyawan Pada PTPN VI Unit Usaha Rimbo Satu Kabupaten Tebo Provinsi Jambi - Fajar Ifan Dolly; Tarjo Tarjo; Rifka Dwi Aulia (STIA Bengkulu, 2024)
This research was conducted to determine whether the effect of work communication on employee performance at PT. Perkebunan Nusantara VI Rimbo Satu Business Unit, effective communication is needed to maintain relationships with employees requiring effective communication. Continuous communication is a must because through communication various matters relating to organizational life are conveyed by one party to another. This study used a quantitative method, namely descriptive analysis with simple linear regression analysis. Data collection techniques used were questionnaires and observation.The population in this study were all employees of PT. Perkebunan Nusantara Rimsa Business Unit which will be sampled is 65 employees.Withdrawal of research samples using the total techniquesample fed up. The results of the study show that the work communication variable (X) has a significant effect on employee performance (Y) with tcount 12.076 > ttable1998 and a significant level of 0.000 ˂ 0.05. The contribution is quite large with a coefficient of determination of 69.8% which can be interpreted that the independent variable work communication (X) has a contribution of 69.8% to the employee performance variable (Y) and 30.2% is influenced by other factors outside the work communication variable (X).